English english - Chintasi Angreani; Nur Afifah; Barkah (Ekspektra : Jurnal Bisnis dan Manajemen, 2024)
Number of digital banking transactions Indonesia based on katadata.com in August 2023 grew by 169,9% throughout the last five years in five years and the amount of third-party banking funds in Indonesia increased by 12.3% according to Indonesian Banking Statistics data for 2020-2022. Number of digital transactions at Bank Maybank Indonesia in 2022 increased by 28% and the number of accounts increased in 2022 by 34%, however the amount of funds raised by Bank Maybank Indonesia decreased by 1.19%. It is alleged that the acquisition of accounts is not followed by customers who retain. This study was conducted to explore the effect of artificial intelligence banking and personal interaction quality on customer retention with customer satisfaction as an intervening variable. The research sample was 215 customer respondents using questionnaires and interviews. The analysis method uses Structural Equation Models Partical Least Square (SEMPLS) based on Smart Partial Least Square (Smart PLS) 3.2.9. The results of the study are artificial intelligence banking has a significant effect on customer retention, personal intelligence banking does not have a significant effect on customer retention. When mediated by customer satisfaction, artificial intelligence banking still has a significant effect on customer retention and personal intelligence banking has a significant effect on customer retention through customer satisfaction as an intervening variable.